2014
DOI: 10.1021/am504124a
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Composite Particles as Solid-Stabilizers for Effective Oil Harvesting

Abstract: The polymer-grafted magnetic composite particles have been synthesized and developed to harvest oil by use of their speical wettability. Different from gravity-driven oil-water separation, the prepared polymer brushes-grafted magnetic composite particles can act as solid-stabilizers that diffuse to the oil-water interfical region and effectively minimize the direct oil-water interfical area by volume exclusion, whereas the magnetic Fe3O4 core allows easy separation of Pickering emulsions from oil-water mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 23 publications
(29 reference statements)
0
78
0
Order By: Relevance
“…Nonetheless, their lower MR performance compared to the CI based MR fluids needs to be 70 improved. Chen et al 81 synthesized polymer-coated magnetite composites to harvest oil to form a Pickering emulsion owing to their special wettability, and reported that magnetic field-responsive composites can separate easily from oil/water mixtures; hence, 75 they can be used in practical applications, such as oil recycling. Zhou et al 82 prepared silica nanoparticles with hydrophobic and hydrophilic properties and demonstrated efficient interfacial catalysts of the obtained amphiphilic silica nanoparticles with ethylene glycol by acting as a stabilizer in Pickering emulsions.…”
Section: Siomentioning
confidence: 99%
“…Nonetheless, their lower MR performance compared to the CI based MR fluids needs to be 70 improved. Chen et al 81 synthesized polymer-coated magnetite composites to harvest oil to form a Pickering emulsion owing to their special wettability, and reported that magnetic field-responsive composites can separate easily from oil/water mixtures; hence, 75 they can be used in practical applications, such as oil recycling. Zhou et al 82 prepared silica nanoparticles with hydrophobic and hydrophilic properties and demonstrated efficient interfacial catalysts of the obtained amphiphilic silica nanoparticles with ethylene glycol by acting as a stabilizer in Pickering emulsions.…”
Section: Siomentioning
confidence: 99%
“…The control of Pickering emulsions plays a pivotal part in many significant processes, for example, oil extraction and recovery [29,30], emulsion polymerization [31,32,33,34], and heterogeneous catalysis [35,36,37]. In this regard, many endeavors have been made in developing controllable Pickering emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Such switchable emulsions have potential applications in colloidal science and engineering, for clearance of chemicals, drug delivery, switchable optical sensing, designing on–off optoelectronic devices, biocatalyst, or colloidal shape control . So far, switchable emulsions have been designed using oil‐in‐water or water‐in‐oil emulsions which are stabilized by switchable emulsifiers, which activate or deactivate upon the action of specific external stimuli such as pH, gas bubbling, light, or magnetic field . However, the use of water‐in‐oil emulsions enforces the switching mechanism to be a two‐step process, since the separated liquids need specific mechanical treatments such as sonication or gas bubbling to return to the initial emulsion form, restricting the practical applications.…”
mentioning
confidence: 99%